(untitled) (European Journal of Interdisciplinary Research and Development, 2026)
An analysis of global trends in the development of the digital economy and financial technologies has revealed an intensification of the digitalization of financial assets due to the emergence of new types of digital tools in addition to key digitalization technologies in financial asset management, such as blockchain, artificial intelligence, and big data. This article examines the role of digital technologies as a key factor in improving the efficiency of financial asset management in the context of the digital transformation of the economy. The article analyzes the main areas of digital solution implementation in the financial and economic activities of organizations, including the automation of financial processes, the use of analytical tools, digital platforms, and information systems to support management decisions. Particular attention is paid to the impact of digital technologies on increasing the transparency of financial transactions, reducing transaction costs, and improving the quality of financial asset management. It concludes that digitalization is essential for ensuring sustainable development and enhancing the competitiveness of organizations in the context of the emerging digital economy of Uzbekistan.